Dual effect of histone H4 on prothrombin activation. (11th August 2016) - Pozzi, N.; Di Cera, E.
Abstract : Essentials Prothrombin converts slowly to thrombin upon interaction with histone H4. Histone H4 may also affect the reactivity of prothrombin toward factor Xa. Histone H4 enhances or inhibits activation by factor Xa depending on cofactor Va. The results reveal an unanticipated dual effect of histone H4 on prothrombin activation by factor Xa. Summary: Background: Recent studies have documented the ability of prothrombin to convert to the mature protease thrombin upon interaction with histone H4. The effect is abrogated by mutation of the catalytic Ser and requires the Gla domain. Objectives: To explore the effect of histone H4 on the reactivity of prothrombin to its physiological activator factor (F) Xa, free or assembled in the prothrombinase complex. Methods: The effect of histone H4 on prothrombin activation by FXa and prothrombinase is studied with kinetic assays. The potential epitope of prothrombin recognizing histone H4 is explored with electrostatic calculations using recent crystal structures. Results and Conclusions: Binding of histone H4 has a dual effect on prothrombin activation by FXa that is of mechanistic significance: it enhances the reaction > 10‐fold in the absence of cofactor Va, but produces complete inhibition in the presence of cofactor. Histone H4 binding to prothrombin produces very slow autoactivation independent of the coagulation cascade and promotes slow thrombin generation by FXa in the absence of phospholipids. In addition, histone H4 has a rapid and drastic inhibitory effect on prothrombin activation by prothrombinase that is likely to dominate pathophysiology.